Antiliver Fibrosis Formula of Fuzheng Huayu Alleviates Inflammatory Response. (12th November 2022) - Chang, Qing-Qi; Pan, Yi-Feng; Yang, Jia-Yi; Li, Rong-Sheng; Yuan, Chun-Lu; Liao, Ya-Fang; Zhang, Dan-Dan; Liu, Cheng-Hai
Abstract : Fuzheng Huayu's (FZHY) formula ameliorated liver fibrosis in clinical and experimental practice. Based on the close link between fibrosis and inflammation, its anti-inflammatory effect and related mechanisms were explored in this present study. With the aid of the inflammatory macrophage model, FZHY significantly blocked nitrite accumulation without observable cytotoxicity due to its suppression of inducible nitric oxide synthase (iNOS) gene and protein expressions in a concentration-depended manner. Proinflammatory mediators including IL-6, CD86, and CD40 were also restrained by FZHY. Interestingly, FZHY induced anti-inflammatory mediators heme oxygenase 1 (HO-1) and peroxisome proliferator-activated receptor γ (PPAR- γ ) expressions simultaneously. Downregulation of iNOS and miR-155 and upregulation of PPAR- γ were also observed in CCl4 -induced liver fibrosis mice upon FZHY administration. Mechanically, FZHY strikingly eliminated the phosphorylation of STAT1 and MAPK. Taken together, FZYH regulated the balance of proinflammatory and anti-inflammatory mediators partially via modulating STAT1/MAPK pathways and the miR-155/PPAR- γ axis.